SCIENTIFIC APPROACHES TO THE RESEARCH OF FEMALE CRIME - Khodjayev Shokhruh Muzaffarovich (Scholar Express Journals, 2023)
This article discusses scientific approaches to the study of female crime. Historical sources, scientific views of national and foreign scientists are studied. Based on the above analysis, the article puts forward a number of proposals and recommendations for legislation and law enforcement practice
Keywords: crime; female crime; criminology; punishment; act